The complete book of drawing skills inspiring instruction from the world's best-selling drawing teacher - Barber, Barrington (London Arcturus Publishing, 2007)
"In this comprehensive guide to the world of drawing, acclaimed teacher Barrington Barber leads you through the major challenges faced by every artist. The complete book of drawing skills shows you how to recognize form and shape, tackle perspective and imbue your subjects with expression." -- Provided by publishers
Includes index.
Keywords: Drawing -- Technique